REFORMISME HUKUM: PENGAMALAN AGAMA PERSPEKTIF SALAFI WAHABI - Endang Madali (LPPM Universitas Bina Bangsa, 2021)
This research proves that Salafism-Wahhabism tends to bring out the problem of aqidah instead of the problem of khilāfīyah. Furthermore, the followers of Salafism-Wahhabism have been well known as a denomination with fundamentalism-literalism world view, and they often conduct rigid and non-contextual interpretation of the Qur’an and Hadith. Therefore, it can be concluded that coercion in religion is directly proportional to the rigidness of religious teachings. And that fiqh must be the basic means of Islamic daʻwah (missionary activities), and it should not be the cantilever of partial daʻwah, which could bring Islamic negative image among non-believers and distancing sinful Muslims from his God. Also, traditional law must be adapted with religious idealism and imbued with the general principles of sharia. Therefore, the sharia perfection could only be realized by the conciliation with constantly-changing social condition and human interests. The researcher used sociology-anthropology approach, which was a religious approach that correlated with some other social sciences approaches such as socio-cultural, normative theology, faith, and religious practices. The researcher used library research as the source of data, and the secondary data sources included the works of Wahhabism scholars that referenced by the followers of Salafism-Wahhabism. The researcher also included the works of scholars that criticized the teachings of Ibn Taymīyah and Muḥammad ibn ‘Abd al-Wahhāb. As the comprehensive research, the researcher used documentation study and conducting deep interview with certain parties and individuals.